2015
DOI: 10.1080/01616412.2015.1115212
|View full text |Cite
|
Sign up to set email alerts
|

The association of HLA-DRB1 and HLA-DQB1 alleles with genetic susceptibility to multiple sclerosis in the Slovak population

Abstract: This is the first study performed to analyse the association of HLA-DRB1/DQB1 with susceptibility to MS in Slovakia. The results of our study confirm that HLA class II alleles, genotypes and haplotypes are associated with MS risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
9
0
2
Order By: Relevance
“…The main HLA associations in this study were HLA‐DRB1*15:01, HLA‐DQB1*06:02, DQB1*06:03 , and DQB1*02:01 . HLA‐DRB1*15:01 and DQB1*06:02 remain the most reported associations with MS in different ethnic groups . Other HLA alleles were also reported in certain ethnic groups, including DRB1*0301 , DQB1*0201, DRB1*0405, and DQB1 * 0301 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The main HLA associations in this study were HLA‐DRB1*15:01, HLA‐DQB1*06:02, DQB1*06:03 , and DQB1*02:01 . HLA‐DRB1*15:01 and DQB1*06:02 remain the most reported associations with MS in different ethnic groups . Other HLA alleles were also reported in certain ethnic groups, including DRB1*0301 , DQB1*0201, DRB1*0405, and DQB1 * 0301 .…”
Section: Discussionmentioning
confidence: 90%
“…HLA-DRB1*15:01 and DQB1*06:02 remain the most reported associations with MS in different ethnic groups. [24][25][26][27] Other HLA alleles were also reported in certain ethnic groups, including DRB1*0301, DQB1*0201, DRB1*0405, and DQB1*0301. [28][29][30] There are few studies coming from the Arab world on HLA associations with MS.…”
Section: Discussionmentioning
confidence: 99%
“…HLA‐DQB1 alleles have diverse effects on susceptibility to autoimmune diseases. A stronger association between the DQB1 *06 alleles and disease susceptibility and a lower frequency of the DQB1 *03 alleles were observed in multiple sclerosis . Similar studies on HLA‐DQB1 polymorphisms showed a higher risk of type I diabetes among individuals with the DQB1 *0201/*0302 alleles, whereas the DQB1 *0301, DQB1 *0601,* DQB1 *0602, DQB1 *0603, and DQB1 *05 alleles protect against the development of type I diabetes .…”
Section: Discussionmentioning
confidence: 56%
“…In addition, we also found that HLA-DRB1/DQB1 class II alleles DRB1*07, DRB1*13, DQB1*03, genotypes DRB1*13/*11, DQB1*05/*03 and haplotypes DRB1*13-DQB1*06 and DRB1*11-DQB1*03 are associated with the protection against MS development. We cannot exclude that the proposed protective effects of the DRB1*11-DQB1*03 and DRB1*13-DQB1*06 haplotypes in our cohort could be, at least partially, due to the linkagedisequilibrium with alleles in the HLA class I region which is primarily associated with MS [41].…”
Section: Hla Genes and Msmentioning
confidence: 88%